Educación de postgrado para fisioterapeutas en el Ecuador - Rosas Mora, Mónica (2022)
The purpose of this work is to examine the offer of postgraduate programs for the physiotherapy area in Ecuador in order to show its status and sufficiency. Costs, modality, duration of the offer and location are reviewed. At the same time, it analyzes the reality of the academic training of physical therapists. The sample used to carry out the study was made up of 100 physical therapists. Measurements and data collection interventions consisted of a survey. It is shown that the universities that offer these programs require more projection and monitoring regarding the positioning of these professionals against the demands of the national and global environment.